ChemInform Abstract: Synthesis, Biological Activity of Thiazolidinones Bearing Indoline Moiety and Isatin Based Hybrids. Issue 24 (June 2015) - Havrylyuk, Dmytro; Zimenkovsky, Borys; Lesyk, Roman
Abstract: Review: 78 refs.